Pembelajaran Seni Budaya Di SMP Zion Makassar: Studi Kasus Kompetensi Guru Non-Seni Budaya Di Kelas IX - Lesta Mega; Andi Ihsan; Heriyati Yatim (Penerbit dan Percetakan, CV. Picmotiv, 2025)
The results of this study indicate that JS teachers have succeeded in developing pedagogical competence significantly, which is reflected in the integration of learning in the cognitive, affective, and psychomotor domains. The arts and culture learning that is implemented is not only oriented towards fulfilling the curriculum, but also functions as a means of strengthening character, developing creativity, and instilling an appreciative attitude towards cultural diversity. Despite having a non-art background, JS teachers are able to overcome the limitations of mastery of the material through a learning ethos, critical reflection, and continuous adaptation. This success is also supported by social competence in building humanistic interactions and creating a fair and communicative learning ecosystem. Thus, JS teachers become representatives of professional educators who are able to transform challenges into meaningful and transformative learning opportunities.